The Good Cop : a mystery - Parks, Brad, 1974- (Parks, Brad, 1974- Carter Ross mystery., 2013)
In the fourth in Brad Parks's award-winning series, Newark investigative journalist Carter Ross must uncover the truth behind a beloved cop's alleged suicide.